2019
DOI: 10.1136/bcr-2019-231634
|View full text |Cite
|
Sign up to set email alerts
|

Management of penetrating injury with retained intraocular lead foreign body from a writing instrument: surgical video with implications for paediatric public health and safety

Abstract: Penetrating ocular injuries from writing instruments that are thrown, especially by children, in the community can result in significant ocular morbidity. Often these cases present to the accident and emergency department. Accurate and prompt assessment is key in saving sight. We present a case of one such injury and how it was surgically managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…One the other hand, preschool children are given more attention and care from their families and society. Accordingly, a study conducted by the British Eye Surveillance Unit confirmed that most eye injuries in children in the UK occur in environments where direct supervision of affected children is expected (at their own homes, other homes, schools, or daycare centres), while very few such injuries occur in relatively unsupervised places (public places or sports facilities) [ 18 ]. Furthermore, since older children and adolescents have an expansive range of independent activities and opportunities to satisfy their curiosity, they are especially vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…One the other hand, preschool children are given more attention and care from their families and society. Accordingly, a study conducted by the British Eye Surveillance Unit confirmed that most eye injuries in children in the UK occur in environments where direct supervision of affected children is expected (at their own homes, other homes, schools, or daycare centres), while very few such injuries occur in relatively unsupervised places (public places or sports facilities) [ 18 ]. Furthermore, since older children and adolescents have an expansive range of independent activities and opportunities to satisfy their curiosity, they are especially vulnerable.…”
Section: Discussionmentioning
confidence: 99%